Simple replantation protocol to avoid ankylosis in teeth intended for orthodontic treatment - Yuli Nugraeni; David Buntoro Kamadjaja; Haryono Utomo (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Dento-alveolar trauma resulted from accidents involving the oral regions mostly affect the upper central incisors. Overjet that is beyond 5 mm and incompetent lip also contribute to increase the risk. Several literatures had already discussed different methods of replantation of avulsed teeth. However, it was not meant for further orthodontic treatment. Purpose: The objective of this review is to propose a simple replantation protocol of avulsed teeth which also prevent from ankylosis. Reviews: Protruded teeth usually need orthodontic treatment; therefore, an appropriate management should be done to avoid the development of ankylosis. Ankylosis of the periodontal ligament (PDL) becomes a problem in orthodontic tooth movement in repositioned or replanted teeth. In addition, ankylosed teeth also more susceptible to root resorption. Actually, it was caused by the endodontic treatment. In particular, severely protruded or unoccluded teeth are hypofunctional, therefore have narrow PDL, thus it may facilitate to ankylosis development. Ideal management protocol such as the use of root canal sealer i.e. mineral trioxide aggregate (MTA); the using of Emdogain, and resilient wiring or semi-rigid fixation with brackets has become a solution in avulsed teeth arranged for orthodontic treatment. Nevertheless, the presence of oral surgeon, endodontist and orthodontist in the same time, and also ideal preparations after an accident was difficult to achieve. Conclusion: Considering that reducing the ongoing PDL inflammation with intracanal medicaments and maintaining the functional force during mastication is possible; it is concluded that this simple replantation protocol is likely.